2013
DOI: 10.3892/mmr.2013.1537
|View full text |Cite
|
Sign up to set email alerts
|

Acid-induced cell injury and death in lung epithelial cells is associated with the activation of mitogen-activated protein kinases

Abstract: Abstract. Gastric hydrochloric acid (HCl) has been regarded as a causative factor of acute lung injury (ALI). The activation of mitogen-activated protein kinases (MAPKs) has been suggested to be a mechanism involved in the pathogenesis of ALI in vivo. However, the effects of HCl on MAPK activation in lung epithelial cells remain to be fully elucidated. Further investigation into the role of MAPK activation in acid-induced cell injury and death is also needed. In the present study, BEAS-2B cells were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Bacterial ( KP ) killing of A549 cells was quantified using a tetrazolium dye reduction assay, as described previously (Chen et al, 2013; Guo & Cheng, 2018). Human lung epithelial cells (A549) were briefly quantified after pneumonia strain and basil using a tetrazolium dye reduction assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial ( KP ) killing of A549 cells was quantified using a tetrazolium dye reduction assay, as described previously (Chen et al, 2013; Guo & Cheng, 2018). Human lung epithelial cells (A549) were briefly quantified after pneumonia strain and basil using a tetrazolium dye reduction assay.…”
Section: Methodsmentioning
confidence: 99%
“…Countess cell counter was used to quantitate cells (Invitrogen, Carlsbad, CA). The experiments were performed in quadruplicate (Chen, Huang, Yang, & Qiu, 2013).…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Certain studies have indicated that members of the MAPK signaling pathway, including ERK, p38 MAPK and JNK, are important in signal transduction pathways activated by stimuli and mediate a number of physiological and pathological changes in cell function (29). The MAPK pathway is also the signal cascade pathway of pro-inflammatory molecules and regulates the inflammatory response through NF-κB activation (30,31). In order to determine the effect of rhBNP in lung fibroblasts under LPS stimulation, the NF-κB pathway was investigated as it is involved in numerous cellular processes, particularly inflammation (32,33).…”
Section: B Amentioning
confidence: 99%
“…Thus there is evidence that in GER children airway damage might be mediated by WAR and AR events through different pathogenetic mechanisms and biochemical profiles. Whilst WAR components can increase airway epithelial cell permeability [25,26] and promote airway epithelial shedding [41,42], exposure to hydrochloric acid and pepsin during AR events can cause acute airway epithelial cell apoptosis and death [43]. Both types of injury are associated with the recruitment and activation of neutrophils that perpetuate the inflammatory, harmful processes.…”
Section: Discussionmentioning
confidence: 99%